2020
DOI: 10.3390/agriculture10090413
|View full text |Cite
|
Sign up to set email alerts
|

Organic but Also Low-Input Conventional Farming Systems Support High Biodiversity of Weed Species in Winter Cereals

Abstract: In recent years, the European Union has been paying particular attention to the problem of biodiversity loss. The possibilities of its assessment and conservation are included in the latest European Union (EU) policies and reflected in the European Biodiversity Strategy. The biodiversity of weeds in winter cereals in organic and conventional low-input farms in Eastern Poland was investigated during a 3-year period. Significantly more species and larger abundance were found in organic than in conventional farmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Farming practice has been identified as the main factor explaining arable plant species diversity and abundance as several studies have stated [22,31,32]. As an important factor for explaining segetal species richness, the management system was accessed concerning its impact on species diversity and species abundances.…”
Section: Spontaneous Arable Weed Floramentioning
confidence: 99%
“…Farming practice has been identified as the main factor explaining arable plant species diversity and abundance as several studies have stated [22,31,32]. As an important factor for explaining segetal species richness, the management system was accessed concerning its impact on species diversity and species abundances.…”
Section: Spontaneous Arable Weed Floramentioning
confidence: 99%
“…It is considered that the greater the diversity in the species composition of a weed community, the less harmful it is to the crop [24,25]. Berbeć et al [4] showed higher species diversity and weed abundance in the ecological system than in the conventional low-input system, but in both farming systems the Shannon-Wiener diversity index had high values, while the Simpson dominance index had low values, indicating their high importance for biodiversity.…”
Section: Biodiversity Of Weeds and Tillage Systemsmentioning
confidence: 99%
“…The large percentage of cereals in the structure of crops in Poland facilitates the growth of segetal plants in arable fields, but the abundance and botanical composition of the associated flora depend primarily on the crop species and habitat conditions [4,5]. Assessment of the diversity of the segetal flora carried out by Sawicka et al [9] showed a higher abundance of weeds in spring wheat and triticale than in winter wheat.…”
Section: Biodiversity Of Weeds In Annual Cropsmentioning
confidence: 99%
See 2 more Smart Citations